2005
DOI: 10.1002/ca.20037
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the appearance of the paraspinal musculoligamentous structures of the cervical spine using ultrasound

Abstract: The application of ultrasound in the imaging of the neck has primarily focussed on anterior structures (e.g., thyroid gland). Structures located on the posterior aspect of the neck have received little attention. This study illustrates the capability of modern ultrasound equipment in visualising the musculoligamentous structures of the neck, particularly the paraspinal musculature. Ten healthy adult volunteers (6 female; 4 male) underwent ultrasound examination of the cervical spine. A standardised technique f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Leung et al (22) showed that the posterior neck muscles and their internal architecture in the cervical spine are easily and effectively imaged. Clear pictures can be gathered of these structures using common modern ultrasound equipment (22). Specific attributes of the musculature such as cross-sectional area, thickness, width, and muscle depth can be visualized in the posterior paraspinal musculature (rectus capitis posterior major, oblique capitis superior, semispinalis capitis, multifidus, erector spinae, and splenius capitis) at rest and during contraction; these measurements were found to be reliable when confirmed against other imaging modalities (21,(23)(24)(25)(26)(27).…”
Section: Musculaturementioning
confidence: 90%
“…Leung et al (22) showed that the posterior neck muscles and their internal architecture in the cervical spine are easily and effectively imaged. Clear pictures can be gathered of these structures using common modern ultrasound equipment (22). Specific attributes of the musculature such as cross-sectional area, thickness, width, and muscle depth can be visualized in the posterior paraspinal musculature (rectus capitis posterior major, oblique capitis superior, semispinalis capitis, multifidus, erector spinae, and splenius capitis) at rest and during contraction; these measurements were found to be reliable when confirmed against other imaging modalities (21,(23)(24)(25)(26)(27).…”
Section: Musculaturementioning
confidence: 90%
“…These topics are also essential to ACI, particularly where an understanding of both the species and individual is a key component of the design and evaluation process [8]. Her experiences of research methods included qualitative methods of surveys and interviews [31], ethological methods of observing and interpreting animal behaviour; and quantitative methods in biomedical engineering to evaluate injury mechanisms [18]. Her introduction to the discipline of ACI stemmed from a collaborative project developing a horse automated behaviour interaction tool [26].…”
Section: Chronological Summarymentioning
confidence: 99%